Workplace violence among Registered Nurses in Saudi Arabia: A qualitative study - Jordan Tovera Salvador; Friyal Mubarak Alqahtani; Maha Mohammed Al‐Madani; Mu'taman Khalil Jarrar; Sherien Ragab Dorgham; Lilibeth Dela Victoria Reyes; Mohammed Alzaid (Wiley, 2021)
Abstract Aim The primary aim of this qualitative inquiry is to explore the experiences of Registered Nurses working in Saudi Arabia, which was a guide to answer the question, "what are the lived experiences of Registered Nurses working in a selected government hospital in Eastern Region of Saudi Arabia towards workplace violence?" Background Workplace violence is a social phenomenon that needs a widespread campaign to eradicate. Incidence from all over the world continues to grow in number, especially among Registered Nurses in Saudi Arabia. Methods Descriptive phenomenology. Purposive‐convenience sampling was used in selecting 21 Registered Nurses as participants for individual in‐depth interviews. Data were gathered over an 11 month's period from September 2017 to August 2018. We used Colaizzi's method for analysing the data. COREQ criteria were adapted in reporting the results of the study. Results Three themes had emerged from the experiences of the participants: "co‐workers become unjust and violent"; "socio‐cultural divergence towards healthcare workers"; and "violence from outside influences affecting the workplace."